THE DEVELOPMENT OF MENTAL MODEL OF PEOPLE WITH VISUAL IMPAIRMENT - Kroupova, Katerina; Ruzickova, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The Development of mental model of people with visual impairment in spatially-orientational and cultural-historical context, is longer Title of the Post. The ability to create mental models is, for people with visual impairment, one of the basic preconditions for the use of available information from the environment and in all areas of everyday life. Tactile graphics can provide one of the means for the development of imagination; they are particularly suitable for the creation of a complex picture of a given situation and its processing into supporting information. Their facilitating function in the development, refinement and consolidation of the imagination is indisputable and proven by empirical studies. The purpose of this paper is to present the application possibilities of three-dimensional displays of haptic information for the purposes of spatial orientation, as well as access to cultural and historical objects with emphasis on the formation of mutual relations and connections within the knowledge base of each individual with visual impairment.